The current image of single SnO2 nanobelt nanodevice studied by conductive atomic force microscopy - Wang Shujie; Cheng Gang; Cheng Ke; Jiang Xiaohong; Du Zuliang (Nanoscale Research Letters, 2011)
Abstract A single SnO2 nanobelt was assembled on a pair of Au electrodes by electric-field assembly method. The electronic transport property of single SnO2 nanobelt was studied by conductive atomic force microscopy (C-AFM). Back-to-back Schottky barrier-type junctions were created between AFM tip/SnO2 nanobelt/Au electrode which can be concluded from the I-V curve. The current images of single SnO2 nanobelt nanodevices were also studied by C-AFM techniques, which showed stripes patterns on the nanobelt surface. The current images of the nanobelt devices correlate the microscopy with separate transport properties measurement together.